2001
DOI: 10.1152/jappl.2001.90.2.665
|View full text |Cite
|
Sign up to set email alerts
|

Adrenergic airway vascular smooth muscle responsiveness in healthy and asthmatic subjects

Abstract: The purpose of the present study was to determine the responsiveness of airway vascular smooth muscle (AVSM) as assessed by airway mucosal blood flow (Qaw) to inhaled methoxamine (alpha(1)-agonist; 0.6-2.3 mg) and albuterol (beta(2)-agonist; 0.2-1.2 mg) in healthy [n = 11; forced expiratory volume in 1 s, 92 +/- 4 (SE) % of predicted] and asthmatic (n = 11, mean forced expiratory volume in 1 s, 81 +/- 5%) adults. Mean baseline values for Qaw were 43.8 +/- 0.7 and 54.3 +/- 0.8 microl. min(-1). ml(-1) of anatomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
37
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 25 publications
7
37
0
2
Order By: Relevance
“…Furthermore, in the present study we have demonstrated that the perfusion flow rate in the IPL is sensitive to high concentrations of ICS and that the selective α 1 -adrenoceptor antagonist prazosin reduced the budesonide-induced vasoconstriction by about 50%, which suggest that the effect of budesonide is mediated through the α 1 -adrenoceptor [9,10]. Hence, in our model we hypothesise that the selective α 1 -adrenoceptor antagonist prazosin competes with NA at the binding sites of the α 1 -adrenoceptor within the lung vessels, and thus, renders the pressor effect induced by budesonide less pronounced.…”
supporting
confidence: 65%
See 2 more Smart Citations
“…Furthermore, in the present study we have demonstrated that the perfusion flow rate in the IPL is sensitive to high concentrations of ICS and that the selective α 1 -adrenoceptor antagonist prazosin reduced the budesonide-induced vasoconstriction by about 50%, which suggest that the effect of budesonide is mediated through the α 1 -adrenoceptor [9,10]. Hence, in our model we hypothesise that the selective α 1 -adrenoceptor antagonist prazosin competes with NA at the binding sites of the α 1 -adrenoceptor within the lung vessels, and thus, renders the pressor effect induced by budesonide less pronounced.…”
supporting
confidence: 65%
“…This would indicate that noradrenergic signalling was involved in the corticosteroid sensitive regulation of smooth muscle tone in airway vasculature [9,10].…”
Section: A C C E P T E D Article In Pressmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings have now been confirmed in human subjects using recently invented noninvasive methods for airway blood flow measurements [20][21][22][23]. By measuring the uptake of an inhaled, soluble inert gas (dimethyl-ether, DME) [24,25], mean airway mucosal blood flow values (comprising about 70% of total airway blood flow) were 24% to 77% higher in patients with stable asthma than in healthy controls [20,23]. Using acetylene rather than DME for 6 measurements, airway blood flow has been confirmed to be elevated in patients with mild persistent and moderate asthma compared with healthy subjects [26].…”
Section: Airway Blood Flow In Asthmamentioning
confidence: 63%
“…In anima l models of airway inflammation such as Ascaris suum sensitized sheep, antigen challenge has been shown to cause an increase in airway blood flow [18,19]. These findings have now been confirmed in human subjects using recently invented noninvasive methods for airway blood flow measurements [20][21][22][23]. By measuring the uptake of an inhaled, soluble inert gas (dimethyl-ether, DME) [24,25], mean airway mucosal blood flow values (comprising about 70% of total airway blood flow) were 24% to 77% higher in patients with stable asthma than in healthy controls [20,23].…”
Section: Airway Blood Flow In Asthmamentioning
confidence: 89%